Study of a tap failure at the internal threads machining. (June 2019) - Monka, Peter; Monkova, Katarina; Modrak, Vladimir; Hric, Slavomir; Pastucha, Peter
Abstract: The article aims to study a tap failure during the internal threads making. Within the research, the synergic effects of cutting speed and helix angle on the durability of selected taps have been investigated including detection of the types tool wear that occurred during the machining. The C45 steel has been selected for the study as a standard machined material used at the long-term durability tests. Three types of taps for M12 thread making with three different helix angles ω  = 0°, 15°, and 35°, all with cutting cone type C, were used during the experiments. The experimental study was carried out in several steps. At the beginning, the preliminary tests were done to be verified the input parameters related to both machined material and tool geometry. In the main phase of the experiments, tool life was investigated at the cutting speed recommended by the tool supplier and after that also at the higher cutting speeds. Within the research, the equations that describe the dependencies of tool durability and threaded length on both observed parameters have been developed based on the experimentally obtained data. The vibro-diagnostic of the taps was carried out because of process stability monitoring and the possibility to predict the tool behavior at the machining with early identification a tool failure. The results have shown that the intensity of tool wear is affected not only by cutting speed but also by the pitch angle of the tap. Next findings confirmed that the tap failure can appear in various forms and that it is possible to identify the presence of tap wear by means of vibro-diagnostics. Highlights: A breakage of the thread making tool may ruin the almost finished workpiece or cause a large downtime. The dependencies of tool durability and threaded length on both cutting speed and helix angle have been developed. Several types of tool wear have appeared at the internal thread making that is a reason of the worse quality of machined surface and deformed threads. Vibrio-diagnostic of taps was carried out because of process stability monitoring and predicting the tool behavior.